Myelotomy promotes locomotor recovery in rats subjected to spinal cord injury: A meta-analysis of six randomized controlled trials - Chuan Qin; Wen-Hao Zhang; De-Gang Yang; Ming-Liang Yang; Liang-Jie Du; Jian-Jun Li (Neural Regeneration Research, 2018)
Objective: To investigate the effects of myelotomy on locomotor recovery in rats subjected to spinal cord injury. Data Sources: Electronic databases including PubMed, Science Citation Index, Cochrane Library, China National Knowledge Infrastructure, Chinese Journals Full-text Database, China Biology Medicine disc, and Wanfang Database were searched to retrieve related studies published before September 2017. The MeSH terms (the Medical Subject Headings) such as “myelotomy”, “spinal cord injuries”, “rats”, “randomized controlled trial” and all related entry terms were searched. Data Selection: Randomized controlled trials using myelotomy for the treatment of acute spinal cord injury in rats were included. Basso, Beattie, and Bresnahan scores were adopted as the evaluation method. RevMan Software (version 5.3) was used for data processing. The χ2 and I2 tests were used to assess heterogeneity. Using a random-effects model, a subgroup analysis was conducted to analyze the source of the heterogeneity. Outcome Measures: Basso, Beattie, and Bresnahan scores were observed 1–6 weeks after spinal cord injury. Results: Six animal trials were included, using a total of 143 lab rats. The included trials were divided into two subgroups by injury degrees (moderate or severe). The pooled results showed that, 1–6 weeks after spinal cord injury, the overall Basso, Beattie, and Bresnahan score was significantly higher in the myelotomy group than in the contusion group (weighted mean difference (WMD) = 0.60; 95% confidence interval (CI): 0.23–0.97; P = 0.001; WMD = 2.10; 95% CI: 1.56–2.64; P < 0.001; WMD = 2.65; 95% CI: 1.73–3.57; P < 0.001; WMD = 1.66; 95% CI: 0.80–2.52; P < 0.001; WMD = 2.09; 95% CI: 0.92–3.26, P < 0.001; WMD = 2.25; 95% CI: 1.06–3.44, P < 0.001). The overall heterogeneity was high (I2 = 85%; I2 = 95%; I2 = 94%; I2 = 88%; I2 = 91%; I2 = 89%). The results in the moderate injury subgroup showed that Basso, Beattie, and Bresnahan scores were significantly higher in the myelotomy group than in the contusion group (WMD = 0.91, 95% CI: 0.52–1.3, P < 0.001; WMD = 2.10; 95% CI: 1.56–2.64, P < 0.001; WMD = 2.65; 95% CI: 1.73–3.57, P < 0.001; WMD = 2.50, 95% CI: 1.72–3.28, P < 0.001; WMD = 3.29, 95% CI: 2.21–4.38, P < 0.001; WMD = 3.27; 95% CI: 2.31–4.23, P < 0.001). The relevant heterogeneity was low. However, there were no significant differences in Basso, Beattie, and Bresnahan scores between the myelotomy and contusion groups in the severe injury subgroup at 2 and 3 weeks after the injury (P = 0.75; P = 0.92). Conclusion: To date, this is the first attempt to summarize the potential effect of myelotomy on locomotor recovery in rats with spinal cord injury. Our findings conclude that myelotomy promotes locomotor recovery in rats with spinal cord injury, especially in those with moderate injury.